Analisis Kadar Glukosa pada Kentang Rebus (Solanum Uberosum) sebagai Pengganti Nasi Bagi Penderita Diabetes Melitus dengan menggunakan Spektrofotometri - Lutfi Lutfi; Dwi Utami Hafriana (Jurnal Media Laboran, 2020)
Glucose has many benefits and functions that we need to know, one of which is as an important nutrient without which humans will not have the energy to carry out all activities, but when consumed in excess it can cause harm to the body. The main source of carbohydrates in food comes from plants and only a few are included in animal foods. For example, potatoes, potatoes can be used as an alternative food for people with diabetes mellitus because it can be a substitute for rice. The purpose of this study was to determine the level of glucose in boiled potatoes (Solanum tuberosum) as a substitute for rice for people with diabetes mellitus using spectrophotometry. The samples were analyzed in two types of potatoes. Determination of glucose levels was carried out by UV-Vis spectrophotometry with a maximum wavelength of 540 nm. From the results of the study, sample A had a glucose level of 7.9951 mg/100 gram, while sample B had a glucose level of 8.0682 mg/100 gram. Based on the results of the study, it can be suggested for further researchers to conduct further research on nutritional content, protein content, fat or glucose level analysis using quantitative and qualitative analysis on other types of potatoes